2002
DOI: 10.1108/00346650210445730
|View full text |Cite
|
Sign up to set email alerts
|

Organic okro (Abelmoschus esculentus): its growth, yield and organoleptic properties

Abstract: Okro (Abelmoschus esculentus) was grown in the field and green house and fertilized with organic‐based fertilizer (OBF), organic and chemical fertilizers. Okro soups produced from the okro fruits harvested from the various fertilizers treatments were subjected to sensory evaluation tests. Application of varying rates of organic fertilizers on the greenhouse okro plants showed that 10 tonnes per hectare of organic fertilizer led to significant increases in microbial activities in the root zone and it also gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“… Adding organic manure to the soil led to significant increase in microbial activities in the root zones, (Taiwo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“… Adding organic manure to the soil led to significant increase in microbial activities in the root zones, (Taiwo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The highest values were obtained from compost at the highest level of 15 ton/fed. The increase of vegetative growth resulting from using compost as organic fertilization treatment might be due to the fact that organic matter is considered as an important factor for improving physical, chemical and biological properties of the soil and consequently, increased plant growth parameters (Saber, 1997;Judais andRinaldi, 2001 andTaiwo et al, 2002). Similar results were obtained by Ahmed 2013 Table (3) indicated that, leaf length (cm), number of leaves/plant and leaves dry weight (g) were significantly increased, in both seasons, due to the use of seven treatments of Microbein biofertilizer (M.B.)…”
Section: Vegetative Growth Charactersmentioning
confidence: 99%
“…From the obtained results, it could be discussed as follows: the enhancement in plant growth parameters (stem length, stem diameter, leaves dry weight / seedling and stem dry weight / seedling, as well as, N, P and K% due to fertilizing Khaya seedlings with filter mud as organic manure reflected the positive, biological and physiological roles of organic manures which were explored by many investigators such as, Bohn et al (1985) emphasized that organic matter as a main source of the elements, N, P and S, as well as, contains high content of B and Mo, and bisedes to considered as a source of energy for Azotobacter growth. the use of organic manure minimized nutrients lost by leaching (Saber, 1997) .Also, organic manure increased microbial activities in the root zone by using it to the soil (Taiwo, et al, 2002). Furthermore, Natarajan (2007) and Sreenivasa et al (2010) claimed the organic manures contain growth promoting hormones (IAA and GA), macronutrients, essential micronutrients and beneficial microorganisms.…”
Section: Leaves Dry Weight/ Seedlingmentioning
confidence: 99%